The Evolution and Equilibrium of Copyright in the Digital Age - Frankel, Susy; Gervais, Daniel J. 1963- (Cambridge University Press, 2014)
The digital age has prompted new questions about the role and function of copyright. Internationally, copyright has progressively increased its scope of protection over new technology and modes of distribution. Yet many copyright owners express dissatisfaction and consider that the system is not working for them. Many users of copyright material, and even some owners, consider that copyright gives too much protection and that copyright owners want too much. This book considers how copyright might evolve in the twenty-first century and how it might reach equilibrium between authors, owners, users and those who connect them
Title from publisher's bibliographic system (viewed on 12 Feb 2016)
Keywords: Copyright and electronic data processing; Digital rights management; Urheberrecht; Gleichheit; Konferenzschrift -- 2012 -- Wellington